Islamic Corporate Governance and Islamic Banking Financial Performance - Kusuma, Melia; Rosadi, Samsul (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This study aims to examine the effect of Islamic Corporate Governance on the financial performance of Islamic banks in 2012-2016. The Islamic Corporate Governance area is proxied by the board of commissioners size, Audit Committee Size, Sharia Supervisory Board Size, and frequency of Sharia Supervisory Board meetings. The object of research is Islamic banks in 2012-2016. Sampling technique is judgment sampling, members of the population that meet the criteria are used as samples. The entire sample was taken from 10 Islamic banks. Hypothesis testing techniques use multiple regression analysis. The results of the F test show that all independent variables simultaneously influence financial performance. Based on the results of the t test it can be concluded that the frequency of sharia supervisory board meetings and the size of the audit committee positively influences the financial performance of Islamic banks. While the size of the area and the age of the area does not affect the Financial Performance.